Frequency analysis of surface electrocardiograms (ECGs) in patients with persistent atrial fibrillation: Correlation with the intracardiac ECGs and implications for radiofrequency catheter ablation. Issue 6 (12th February 2014) - Uetake, Shunsuke; Miyauchi, Yasushi; Osaka, Motohisa; Hayashi, Meiso; Iwasaki, Yu‐ki; Yodogawa, Kenji; Horie, Tsutomu; Tsuboi, Ippei; Hayashi, Hiroshi; Takahashi, Kenta; Shimizu, Wataru
Abstract: Background: The nature and significance of the frequency characteristics of the surface electrocardiogram (ECG) in patients with persistent atrial fibrillation (AF) undergoing radiofrequency ablation are unclear. Methods: Preablation surface and intracardiac ECGs were obtained using offline fast Fourier transform (FFT) analysis in 40 patients with persistent AF. For the FFT analysis of the surface f‐wave, the QRS‐T complex was canceled utilizing a template subtraction algorithm. The ablation procedure included isolation of the pulmonary veins (PV) and posterior left atrium and linear ablation of the mitral isthmus and additional lesions using a stepwise approach. Results: The dominant frequency (DF) of all the intracardiac signals, except for the left inferior PV, had a significant correlation with the DFs from the surface electrocardiogram. The strongest correlation was observed between the DFs of the left atrial appendage (LAA) and those on the limb leads (correlation coefficient, 0.802–0.882, P <0.001) and between the DFs on the right atrial appendage and those on lead V1 (correlation coefficient, 0.86, P <0.0001). After radiofrequency ablation, AF was terminated in 23 patients and persisted in the remaining 17. The best electrographic predictor of AF termination was the DFs in the LAA (DF<6.5 Hz, sensitivity 75%, specificity 86%) and lead II (DF<5.9 Hz, sensitivity 82%, specificity 78%), respectively. Conclusions: The frequency characteristics of the surface ECG correlated with those of the intracardiac signals, and the DF predicted termination of AF during radiofrequency ablation in patients with persistent AF.